A study protocol for a phase II randomised, double-blind, placebo-controlled trial of sodium selenate as a disease-modifying treatment for behavioural variant frontotemporal dementia. Issue 11 (16th November 2020) - Vivash, Lucy; Malpas, Charles B; Churilov, Leonid; Walterfang, Mark; Brodtmann, Amy; Piguet, Olivier; Ahmed, Rebekah M; Bush, Ashley I; Hovens, Christopher M; Kalincik, T; Darby, David; Velakoulis, Dennis; et al.
Abstract : Introduction: Behavioural variant frontotemporal dementia (bvFTD) is a neurodegenerative disorder often neuropathologically associated with the accumulation of abnormally hyperphosphorylated tau, for which there is currently no disease-modifying treatment. Previous work by our group has shown sodium selenate upregulates the activity of protein phosphatase 2 in the brain, increasing the rate of tau dephosphorylation. The objective of this study is to evaluate the efficacy and safety of sodium selenate as a disease-modifying treatment for bvFTD. Methods and analysis: This will be a multisite, phase IIb, double-blind placebo-controlled trial of sodium selenate. One hundred and twenty participants will be enrolled across 4 Australian academic hospitals. Following screening eligible participants will be randomised (1:1) to sodium selenate (15 mg three times a day) or placebo for 52 weeks. Participants will have regular safety and efficacy visits throughout the study period. The primary study outcome will be percentage brain volume change (PBVC) as measured on MRI over 52 weeks of treatment. This will be analysed with a general linear model (analysis of covariance (ANCOVA)) with the PBVC as an output, the treatment as an input and the baseline brain volume as covariate for adjustment purposes. Secondary outcomes include safety and tolerability measures, and efficacy measures; change in cerebrospinal fluid total-tau, Addenbrooke's Cognitive Examination-III and Cambridge Behavioural Inventory-Revised scores over the 52 weeks of treatment. These will also be analysed with ANCOVA where the corresponding baseline measure will be incorporated in the model. Additional exploratory outcomes will include other imaging, cognitive and biospecimen analyses. Ethics and dissemination: The study was approved by the Human Research and Ethics Committee of the lead site as part of the Australian Multisite Ethics approval system. The results of the study will be presented at national and international conferences and published in peer-reviewed journals. Trial registration number: ACTRN12620000236998 .